AS FRAGILIDADES DO SISTEMA DE LICENCIAMENTO AMBIENTAL NO BRASIL COM BASE NO ESTUDO DE CASO DA COMPANHIA SIDERÚRGICA DO ATLÂNTICO - Brasileiro Pena, Caroline; Lameck Pinheiro, Aleson; Felipe Saraiva, André; Paulo Rodrigues, João; Amaral Adler Rodrigues, Luiza (LINKSCIENCEPLACE, 2026)
One of the most important instruments of the environmental protection policy is the Environmental Licensing. However, the licensing process in the country has many weaknesses resulting from the contrast between theoretical proposals and their implementation. Thus, this study aims to analyze the Environmental Licensing in Brazil and discuss some of the debilities found in that process. For this, the case study of Companhia Siderúrgica do Atlântico (CSA) was used to present some of the problems arising from these oversights in the Rio de Janeiro state. From the joint analysis of the theory and practice of licensing, it was found that the process in question suffers much political influence, which overlaps the technical guidelines, and economic motivations are prioritized over the interests of the population.